Doping of erbium and silver in zinc tellurite glass system for optical application - Shahrol Nidzam, Nazirul Nazrin (2020)
The improvement of properties for glass material application in disparate range are open-ended challenges especially in materials science and technology. Although there are researches being executed on lanthanide elements with zinc tellurite glass as parent material, no researchers have tried to assimilate both erbium and silver in a glass system in order to investigate the changes made by the glass materials. To reveal the effect of erbium and silver oxides on structural, physical, elastic, thermal, optical properties as well as the execution of McCumber and Judd-Ofelt theory analysis, four glass series of zinc tellurite glasses that were doped with erbium and silver oxides were successfully synthesized by melt-quenching method. The glasses were prepared based on the chemical composition provided with variation concentration of dopants; 1) [(TeO2)0.7 (ZnO) 0.3]1-x (Er2O3)x, 2) [[(TeO2)0.7(ZnO) 0.3] 0.96 (Er2O3)0.04]] 1-y (Ag2O) y, 3) [(TeO2)0.7 (ZnO) 0.3]1-x (Ag2O)x and 4) [[(TeO2)0.7(ZnO) 0.3] 0.98 (Ag2O)0.02]] 1-y (Er2O3) y where in first, second and fourth glass series, the molar fraction, x = 0.01, 0.02, 0.03, 0.04 and 0.05 whereas in third glass series, x = 0.005, 0.010, 0.015, 0.020 and 0.025. The different dopant’s amount in third glass series were attributed to the less fragility of the glass if low concentration as low as 0.025 is employed. The structural, physical, elastic, thermal and optical properties of the glass samples were elucidated using equipment such as X-ray diffraction (XRD), Fourier transform infrared (FTIR), densimeter, Ultrasonic machine, Differential scanning calorimeter (DSC), UV-Visible (UV-Vis) and photoluminescence spectrometers. Meanwhile, Origin 6.0 had been used for deconvolution and McCumber analysis and spectragryph had been employed for Judd-Ofelt evaluation. The amorphous nature of the prepared glass samples is confirmed from the XRD analysis. In the study of FTIR spectra, the presence of TeO4 was detected while TeO3, ZnO, Er2O3 and Ag2O functional groups were not detected. The non-existence of the remaining functional groups implies that these bonds have been broken down within the glass network. By implementing the deconvolution technique using Origin 6.0 software, the remaining functional groups were found. This phenomenon confirms that there is still a little amount of concentration of the remaining functional groups that can be observed. The density of all glass series is found to increase approximately from 4.0 to 6.0 g/cm3 due to the improvement in the compactness of the glass samples. Nevertheless, the molar volume (Vm) inclines for glasses that consists of erbium oxide as the main dopant while for the glasses that consist of silver oxide as the main dopant, the molar volume decreases. The inclination of molar volume is attributed to larger bond length of the dopant. On the other hand, the decrement of the molar volume can be theoretically related to the inverse relation between density and molar volume. The elastic moduli and some of the elastic parameters of the glasses are generally found to vary with the increase of erbium oxide and silver oxide while the Poisson’s ratio lies in the expected range of 0.2 to 0.3. The presence of erbium oxide and silver oxide in the glass system make the glass sample becomes compact and rigid due to their larger atomic mass compared to the host glass materials. Besides that, the experimental study of elastic properties has shown the similarities in most of the theoretical elastic including Makishima and Mackenzie model and rocherulle model. The thermal properties were measured for all glass series. The glass stability for most of the glass samples with erbium oxide as the main dopant are been found to exceed 100°C, which is convenient in fiber optic application. The erbium oxide enhances the link of cation-anion in the glass system which will improve the strength of the glass. In terms of optical parameters, the optical band gap, refractive index and metallization criterion display some variation as the dopants were inserted into the glass samples. The band gap of the prepared glasses in this work ranges from 3.0 to 5.0 eV which is suitable for semiconductor device application. Meanwhile, refractive index values of the prepared glasses are found to be around 2.3 to 2.5, which are relatively high due to the presence of non-bridging oxygen, making them useful for laser operation. Metallization criterion with value of 0.30-0.45 guarantees the glasses ability for non-linear application such as optical switching and optical limiting. Blue, green and red emission are found in all glass series under 375 nm excitation wavelength. Intense and broad near infrared 1500 nm emission above 48 to 137 nm FWHM and gain bandwidth within the range of (97 to 625) x 10-28 cm3 had been attained in all glass system except for third glass series. This result suggests that the fabricated glass samples have the potential to become a promising optical material for broadband telecommunication technology. In laser designation, the Judd-Ofelt analysis had been analyzed for all the glass system consisting of rare earth element. Large values of Ω2, Ω4 and Ω6 are strongly related to the improvement of the asymmetrical behavior of erbium ions sites with the formation of higher electron density on the oxygen ligand ion. As a result, strong Er-O covalence is formed with the increasing erbium ions concentration.